Archaeogeophysics State of the Art and Case Studies - El-Qady, Gad.; Metwaly, Mohamed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes the application of non-destructive geophysical methods in subsurface archaeological features. Such non-destructive methods are magnetometry, electrical resistance, electromagnetic conductivity, magnetic susceptibility and ground penetrating radar. This book also includes the last improvements in instrumentations, data processing, and interpretations of the collected data sets leading to the rapid progress in geophysical applications in the field of archaeological investigations. The book also provides complete case-studies and archaeological interpretation obtained our results carried out in different localities around the world.
1. Geophysical Techniques Applied in Archaeology -- 2. Integrated Geophysical Investigations in Archaeological Sites: Case Studies from Turkey -- 3. Application of Tensorial Electrical Resistivity Mapping to Archaeological Prospection -- 4. Combined Seismic Tomographic and Ultra-Shallow Seismic Reflection Study of an Early Dynastic Mastaba, Saqqara,Egypt -- 5. Archaeological Geophysics in Portugal: Some Survey Examples -- 6. Integrated Geophysical Methods for Detecting Archaeological Han Dynasty Tombs -- 7. Geomagnetism Exploration of the Egyptian Archaeology: Thirty-Years of Success and Challenges -- 8. The Utility of Geophysical Models in Archaeology: Illustrative Case Studies -- 9. Ground Penetrating Radar Resolution in Archaeological Geophysics -- 10. The Standardized Pricking Probe Surveying and Its Use in Archaeology -- 11. Geophysical Imaging of an Early Nineteenth Century Colonial Defensive Blockhouse:Applications of EM Directionality and Multi-parameter Imaging -- 12. Geophysical Assessment and Mitigation of Degraded Archaeological Sites in Luxor Egypt -- 13.Integrated Geophysical Techniques for Archaeological Remains: Real Cases and Full Scale Laboratory Example -- 14. What Is Conservation Plan?.
Keywords: Geophysics; Archaeology; Geographic information systems; Cultural property; Geophysics; Archaeology; Geographical Information System; Cultural Heritage